Surface Treatment of Wood Polymer Composites from Straw Fiber Using Argon Plasma Jet Injection: Enhancing Adhesion Properties - Harianingsih, Harianingsih; Astuti, Widi; Widyastuti, Catur Rini; Wulandari, Retno; Puzi, Asmarani Ahmad (Jurnal Bahan Alam Terbarukan, 2024)
The increasing demand for environmentally friendly materials has driven research into biodegradable composites. Straw fiber, an abundant agricultural byproduct, remains underutilized as a filler material in Wood Polymer Composites (WPC). To enhance its application potential, this study investigates the surface treatment of straw fiber/polyvinyl alcohol (PVA) matrix composites using a plasma jet with argon injection. The use of cold plasma as a treatment method is expected to improve the interfacial bonding between the straw fiber and the PVA matrix, thereby enhancing composite properties. The research employs several analytical methods, including morphological analysis of straw fibers before and after plasma jet treatment using Scanning Electron Microscopy (SEM), contact angle measurements, and emission intensity analysis via Optical Emission Spectroscopy (OES). The results reveal significant morphological changes in the straw fiber surface after plasma jet treatment, characterized by increased roughness and improved adhesion with the PVA matrix. The emission intensity analysis identifies peak reactive argon species at λ = 698.223 nm to λ = 778.398 nm, N₂⁺ at λ = 386.685 nm to λ = 445.289 nm, N₂ at λ = 324.768 nm to λ = 377.983 nm, and atomic oxygen spectral triplets at λ = 780.341 nm to λ = 830.867 nm. Moreover, the decrease in the contact angle from 90° to 57° over 60 minutes demonstrates a transition in the composite's surface properties from hydrophobic to hydrophilic. These findings highlight the effectiveness of plasma jet treatment in modifying straw fiber surfaces for improved composite performance, paving the way for broader applications of biodegradable WPC materials.